Triazido[tris(2-pyridyl-κN)methylamine]cobalt(III) - Hao, Lujiang (International Union of Crystallography, 2008)
The title compound, [Co(N(3))(3)(C(16)H(14)N(4))], was synthesized by hydrothermal reaction of [Co(NH(3))(6)](NO(3))(3), NaN(3) and tris(2-pyridyl)methylamine. The structure contains two independent complexes in the asymmetric unit, with closely comparable geometry. The Co(III) atoms are hexacoordinated by three N atoms from the tridentate tris(2-pyridyl)methylamine ligands and three azide ions in a fac arrangement. N—H⋯N hydrogen bonds are formed between the amino group and the uncoordinated terminal N atoms of the azide ligands.